Implementation of Homeschooling Management in Supporting an Inclusive Learning Environment at PKBM Think Indonesia School - Lita Kristiana; I Ketut Atmaja Johny Artha; Sjafiatul Mardliyah (Universitas Negeri Semarang, 2026)
This study aims to analyze the implementation of homeschooling management in supporting an inclusive learning environment at the Think Indonesia School Community Learning Center (PKBM) in Sidoarjo. The focus of the study covers the functions of planning, organizing, implementing, and controlling management. This study uses a qualitative approach with a case study method, collecting data through in-depth interviews, observation, and documentation of students, parents, and mentors. The results show that the implementation of homeschooling management at the Think Indonesia School Community Learning Center (PKBM) is effective in creating an inclusive learning environment. Planning is carried out comprehensively through an in-depth initial assessment, including mapping individual potential using the STIFIn instrument, as well as the development of an adaptive curriculum centered on the needs of students. The organization is characterized by a streamlined, functional, and hierarchical structure, with a clear division of tasks to support program specialization. The implementation of learning adopts a flexible hybrid system, with an emphasis on building psychological comfort, a personal approach by mentors, the use of participatory methods, and the integration of vocational skills programs. This approach successfully heals learning trauma, increases independence, and increases intrinsic motivation among students. Continuous control is carried out through monitoring, comprehensive evaluation (academic, psychological, and social), intensive communication with parents, and adaptive follow-up to ensure quality services and individual development. Harmonizing these four management functions has successfully created an alternative educational ecosystem that focuses not only on academic achievement but also on the psychological well-being and optimization of students' potential.